2015
DOI: 10.1590/s1806-92902015001200003
|View full text |Cite
|
Sign up to set email alerts
|

Feeding behavior and productive performance of steers fed pearl millet grain-based diets containing proportions of babassu mesocarp bran

Abstract: -The objective of this study was to evaluate the feeding behavior and feedlot productive performance of dairy-origin steers fed for 84 days ground pearl millet grain-based diets with 0, 120, 240, 360, and 480 g kg -1 of babassu mesocarp bran (BMB) and a standard diet based on ground corn. Thirty Holstein-Zebu steers with average initial body weight of 371.02±27 kg were used. The experimental design was completely randomized, with five replications. Dry matter intake showed better fit with the quadratic regress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 21 publications
1
7
0
Order By: Relevance
“…In this context, millet grain can be utilized at times when corn prices are on the rise, replacing it totally or partially in the cattle diet. This strategy in diet formulation allows for reduction in feed cost in the feedlot while maintaining animal performance and carcass characteristics similar to those obtained with the corn grain diet ALENCAR et al, 2015).…”
Section: Introductionmentioning
confidence: 90%
“…In this context, millet grain can be utilized at times when corn prices are on the rise, replacing it totally or partially in the cattle diet. This strategy in diet formulation allows for reduction in feed cost in the feedlot while maintaining animal performance and carcass characteristics similar to those obtained with the corn grain diet ALENCAR et al, 2015).…”
Section: Introductionmentioning
confidence: 90%
“…In this study, the lack of variations in DM intake with inclusion of BMB might be associated with the inclusion levels of this byproduct that ranged from 7.7 to 11.18% and from 16.43 to 23.81% in the diets with high and low proportions of sugarcane, respectively. Changes in DM intake with the inclusion of BMB in the cattle diets were found when the levels of this byproduct reached values higher than 25% of the diet dry matter (Cruz et al, 2014;Alencar et al, 2015). The high indigestible fiber content and low passage rate of sugarcane may have contributed to the obtained results, altering the transit of BMB through the reticulorumen (reducing its output) due to fiber entanglement.…”
Section: Discussionmentioning
confidence: 93%
“…As for the animal response to BMB inclusion in diets, the literature (Silva et al, 2012;Cruz et al, 2014;Santana et al, 2015) shows that when inclusion levels are low to moderate (226.8 to 422.4 g/kg of the diet DM), no changes in animal performance are observed, reflecting the similar energy intake. Nevertheless, Miotto et al (2013) and Alencar et al (2015) showed that the average daily gain of feedlot cattle began to show a significant decline as the inclusion of BMB approached 500 g/kg of diet dry matter, after which the energy intake did not support the maintenance of animal performance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among feedstuffs to substitute corn grain at times when this commodity is found at high prices, millet grain and babassu mesocarp bran are noteworthy alternatives. The use of these feedstuffs in cattle diets has allowed the reduction of feed costs, with animal performance and carcass characteristics remaining similar to those obtained with corn grain (CRUZ et al, 2014(CRUZ et al, , 2015ALENCAR et al, 2015).…”
Section: Introductionmentioning
confidence: 92%